A case of metastatic endobronchial tumor from uterine leiomyosarcoma. (2022) - Ono, Manabu; Kobayashi, Seiichi; Hanagama, Masakazu; Ishida, Masatsugu; Sato, Hikari; Okutomo, Koji; Endo, Takuto; Shirai, Yusuke; Itakura, Yuko; Yanai, Masaru
Abstract: A 54-year-old woman presented with persistent productive cough, found to have an endobronchial tumor which obstructed the left upper lobe bronchus. Histopathological examination of a transbronchial biopsy of the endobronchial tumor suggested leiomyosarcoma. A positron emission tomography (PET)-CT revealed uterus tumor with moderate uptake of 18 F-fluorodeoxyglucose, suggesting uterine malignancies. From the results of histological findings of the resected uterus and the biopsied bronchial specimen, she was diagnosed with uterine leiomyosarcoma and endobronchial metastasis. The systematic use of PET-CT could be useful for patients presenting with tumors that cause endobronchial metastasis of leiomyosarcomas.